Age‐related biophysical changes of the epidermal and dermal skin in Korean women. Issue 4 (13th February 2019) - Cho, Changhui; Cho, Eunbyul; Kim, Nahee; Shin, Juhee; Woo, Sanga; Lee, Eunyoung; Hwang, Jaesung; Ha, Jaehyoun
Abstract: Introduction: The clinical characteristics of skin were investigated to study the inter‐relationship and changes in the biophysical properties of the epidermal and dermal layers associated with aging using noninvasive methods. Methods: Our study included 100 healthy women aged between the early 20s and late 60s. Biophysical characteristics of skin such as color (brightness and spots), transparency, wrinkle on crow's feet, elasticity, hydration, sebum content, glossiness, and transepidermal water loss measured under controlled conditions. Results: This study performed in a Korean population demonstrated that aging significantly affects human skin in terms of parameters such as wrinkles, skin color, elasticity, and epidermal hydration. Age‐related changes in skin hydration showed varying patterns between the epidermis and dermis. Skin color showed heterogeneous characteristics between the upper and lower epidermal layers associated with aging. Skin elasticity and wrinkles were observed to show and inversely proportional relationship in the early 40s. Conclusions: We confirmed the significant influence of aging on the biophysical properties of skin and determined the distinct age‐related biophysical changes in the epidermal and dermal layers of skin using noninvasive method. This study indicates the need for further research to investigate the distinctive age‐related changes in characteristics of the epidermal and dermal layers of human skin.